2009
DOI: 10.9775/kvfd.2009.790
|View full text |Cite
|
Sign up to set email alerts
|

Anti-coccidiosis Effect of Thymus serpyllum in Rabbits: Oocyst Shedding and Body Weight Changes

Abstract: Thymus serpyllum'un metanolik ekstraktı ve sulfadimidinin antikoksidial aktiviteleri deneysel olarak Eimeria ile enfekte edilmiş tavşanlarda karşılaştırılarak çalışıldı. Bu çalışmada sulfadimidin ve Thymus serpyllum'un metanolik ekstraktının oosist atılımı ve canlı ağırlık değişimleri üzerine etkileri gösterildi. Tavşanlar her birinde 6 hayvan bulunan 3 gruba ayrıldı. I. grup pozitif kontrol grubu (infekte, tedavi edilmemiş grup), II. grup ekstrakt grubu (infekte, Thymus serpyllum'un metanolik ekstraktı ile te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…Yim et al [38] also reported that A. vera extract can be used as a safe dietary supplement against coccidiosis. Some other studies had also reported the similar findings in broilers and rabbits [39][40][41] . Lesion score is the most common method for assessing intestinal condition during coccidiosis [42] .…”
Section: Discussionsupporting
confidence: 78%
“…Yim et al [38] also reported that A. vera extract can be used as a safe dietary supplement against coccidiosis. Some other studies had also reported the similar findings in broilers and rabbits [39][40][41] . Lesion score is the most common method for assessing intestinal condition during coccidiosis [42] .…”
Section: Discussionsupporting
confidence: 78%
“…As an alternative to antibiotics, anticoccidial effect of various herbal extracts has been reported [31,[34][35][36][37][38][39] . Their effects were related to protection and/or relieve of intestinal mucosa.…”
Section: Feed Conversion Ratio (Fcr Feed: Bw Gain)mentioning
confidence: 99%
“…Thymus genus of the family Labiatae consists of Turkey's largest genus (Avci, 2011), and there are 39 species and 59 taxa in this genus with an endemic rate of 53 % (Ozkan et al 2010). Of the member of this species, Thymus praecox is common in Turkey and has a large number of subspecies and varieties (Avci, 2011).…”
Section: Introductionmentioning
confidence: 99%